Anthropic transformation in the Gurupi river basin, eastern Amazon (Sustainability in Debate, 2019)
The objective of this paper was to evaluate the degree of anthropic transformation of a river basin in the Amazon region. We used the digital data of the TerraClass Project to calculate the Anthropic Transformation Index - ATI. In order to verify spatial and temporal changes along a decade in the Gurupi river basin, we used the database of the years 2004 and 2014. The results showed an increase of anthropic changes in the basin over a decade, as a result of forest cover conversion into agricultural and pastures areas. Although the Gurupi river basin remains at a regular level of degradation after a decade, the intensification of land use and land cover change is a threat to the few rainforest remnants of the river basin, which can lead the region to the next level of degradation, if effective forest protection, conservation and restoration actions are not implemented in the region.